Dampak Belanja Pemerintah terhadap Peningkatan Kualitas Pembangunan Manusia di Provinsi Papua - Herlina Irianti Mulyono; Elsyan Rienette Marlissa; Pisi Bethania Titalessy; Sarlota Arrang Ratang (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
This study aims to examine and analyze trends in the quality of human development, budget allocation, spending patterns, and their impacts on improving human development quality in Papua Province. The study uses secondary data obtained from the Regional Development Planning Agency (Bappeda) of Papua Province, the Central Statistics Agency (BPS), Gross Regional Domestic Product (GRDP/PDRB) data, and the Regional Financial and Asset Management Agency (BKAD), and employs descriptive analysis methods. This analysis provides an overview of human development conditions and regional expenditure trends based on education, health, economic, and infrastructure functions. The study seeks to analyze trends in human development quality, examine the relationship between government expenditure and improvements in human development, and assess the impact of government spending on human development outcomes in Papua Province. Furthermore, the analysis identifies leading sectors based on the strength of correlation and examines the effects of government spending on income and labor in supporting the realization of human development in Papua Province.